Un enfoque integrador para la protección del patrimonio histórico, artístico y cultural y los derechos humanos en el ámbito del Derecho Internacional Privado - Alvares García Junior, Armando (Bitácora Millennium DIPr: Derecho Internacional Privado, 2024)
Esta investigación examina la interacción entre el Derecho Internacional Privado, el Derecho Internacional de los Derechos Humanos y el derecho a la propiedad en situaciones de restitución de obras de arte ilegalmente confiscadas. La relevancia y originalidad del estudio se encuentran en su enfoque integrador y transversal, enfatizando la necesidad de un sólido marco legal internacional y una colaboración interdisciplinaria eficaz para proteger adecuadamente el patrimonio cultural y los derechos humanos.
An integrative approach to the protection of historical, artistic and cultural heritage and human rights in the field of Private International Law
his research examines the interaction between private international law, international human rights law and the right to property in situations of restitution of illegally confiscated works of art. The relevance and originality of the study lie in its integrative and cross-cutting approach, emphasising the need for a strong international legal framework and effective interdisciplinary collaboration to adequately protect cultural heritage and human rights. Through the analysis of cases such as Cassirer v. Thyssen-Bornemisza Collection Foundation, the research seeks to offer a novel, modern and up-to-date perspective to address these complex issues and to promote the harmonisation of applicable norms and principles. By investigating the relationships between these legal fields and proposing ingenious legal solutions, this study aims to establish the basis for a more efficient and holistic approach to the resolution of conflicts related to the restitution of works of art and the protection of human rights at the international level, taking private international law as a central element.
Keywords: cooperación internacional; derecho internacional privado; Derechos Humanos; restitución de obras de arte; patrimonio cultural; international cooperation; private international law; Human Rights; cultural heritage; restitution of works of art